Dynamic response of the pressurized laminated composite cylindrical shell subjected to impact loading - Farzin Firouzabadi, 1985-; Amran Ayob, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012